Pengelolaan Pembelajaran Sejarah Pada Masa Pandemi Covid-19 (Studi Kasus di SMAN 73 Jakarta) - Wilda Shifa Fauziyah; Corry Iriani Rochalina; Nurzengky Ibrahim (Universitas Pendidikan Mandalika, 2022)
This research aims to describe the management, which includes planning, implementation, and evaluation of learning history since the Covid-19 pandemic era. This research, which was conducted at SMAN 73 Jakarta, used a qualitative research approach with a case study method. Techniques of data collection were observation, in-depth interviews, and documentation. The data analysis technique, referred to as the Miles and Huberman technique, consists of reducing data, presenting data, and verifying/ making a conclusion. The results showed that the distance learning process went well. Starting with planning for history learning, the teacher designed an emergency lesson plan that the government adjusted. The teacher implemented history learning using learning media that supported the online learning process using WhatsApp groups, Google Classroom, Google Meet, and Zoom meetings. The final learning method is that the teacher evaluates the assessment orally and in writing. The study's results regarding history learning during the Covid-19 pandemic at SMAN 73 Jakarta had quite good preparations in dealing with the Covid-19 emergency. It means that the suitability of the curriculum during the pandemic, the use of methods and learning media during the pandemic, the current learning process evaluation, and supervision of learning have been carried out by school principals and teachers.